2007
DOI: 10.1186/1471-213x-7-118
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization, gene expression and dependence on thyroid hormones of two type I keratin genes (sseKer1 and sseKer2) in the flatfish Senegalese sole (Solea senegalensisKaup)

Abstract: Background: Keratins make up the largest subgroup of intermediate filaments, and, in chordates, represent the most abundant proteins in epithelial cells. They have been associated with a wide range of functions in the cell, but little information is still available about their expression profile and regulation during flatfish metamorphosis. Senegalese sole (Solea senegalensis) is a commercially important flatfish in which no keratin gene has been described yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The processes of skin stratification have been studied in greatest detail in zebrafish, but appear at least structurally similar in cichlids (Sire & Géraudie, 1983). Keratins mediate some of the skin restructuring events, and in flatfish, keratin expression is regulated directly by TH (Infante et al, 2007), decreasing after metamorphic climax (Campinho, Silva, Sweeney, & Power, 2007). The metamorphic transformation of flatfish skin resembles the metamorphic restructuring seen in amphibians (Power et al, 2008), in which keratin loci are also under TH control (Page et al, 2007).…”
Section: Local Mechanisms Of Morphogenetic Changesmentioning
confidence: 99%
“…The processes of skin stratification have been studied in greatest detail in zebrafish, but appear at least structurally similar in cichlids (Sire & Géraudie, 1983). Keratins mediate some of the skin restructuring events, and in flatfish, keratin expression is regulated directly by TH (Infante et al, 2007), decreasing after metamorphic climax (Campinho, Silva, Sweeney, & Power, 2007). The metamorphic transformation of flatfish skin resembles the metamorphic restructuring seen in amphibians (Power et al, 2008), in which keratin loci are also under TH control (Page et al, 2007).…”
Section: Local Mechanisms Of Morphogenetic Changesmentioning
confidence: 99%
“…This highly complex process, which involves drastic morphological and physiological changes in order to become an asymmetric benthic juvenile, is regulated by thyroid hormones (THs) (Manchado et al, 2008). During metamorphosis, several genes involved in central metabolic pathways and cytoskeleton such as the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (Manchado et al, 2007a), keratins (Infante et al, 2007), elongation factor 1 alpha (Infante et al, 2008a), and ribosomal proteins (Manchado et al, 2007b) modify their expression levels. Previous results on the ontogeny of HSP90 in silver sea bream indicated that HSP90 protein levels increased progressively from 1 DAH onwards, resembling the profile of cortisol and not that of THs (Deane and Woo, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Type II keratin, sseKer3 , is highly expressed just before metamorphosis onset and decreases during late metamorphosis . Type I keratin genes, sseKer1 and sseKer2 , also decrease during late metamorphosis . We have identified a truncated type II keratin with a maximum during early ontogenesis and a decrease to a minimum at the end of metamorphosis.…”
Section: Discussionmentioning
confidence: 83%
“…We have identified a truncated type II keratin with a maximum during early ontogenesis and a decrease to a minimum at the end of metamorphosis. In fish, deficient keratinization and the presence of dermal scales and mucus in adult skin is a common phenomenon and an adaptation to the aquatic environment . Type I and II sole keratins are down‐regulated by THs during metamorphosis, suggesting a role in tissue remodeling .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation